Evaluation of Iron Status in Diabetic CKD Stage 5 Pre- Dialysis Patients (BIRDEM Medical Journal, 2013)
Objective: To evaluate the iron status among patients with diabetes mellitus and CKD stage 5, who have not started dialysis yet. Methodology: This cross-sectional study was carried on a total of 50 adult diabetic patients with stage 5 CKD, in the Department of Nephrology, BIRDEM General Hospital, Dhaka over 6 months. Results: Total number of patients was 50. Sixty two percent were male and 38% were female. Mean age was 55.22 (range 33-75) years. Mean± SD hemoglobin and ferritin levels were 7.61±2.54 mg/dl and 155.22±92.32 ng/ml respectively. Seventy percent of the study subjects had haemoglobin level d 9 mg/dl. In 48% of the study subjects, ferritin level was less than 100ng/ml. Fourty six percent of the study subjects had TSAT level below 20%. Haemoglobin, serum ferritin and TSAT level in the study subjects had negative relationship with duration of CKD. Haemoglobin and serum ferritin levels were positively correlated with eGFR of the study population. TIBC level had negative relationship with haemoglobin level which was statistically significant. Serum iron, ferritin and TSAT level in the study subjects were positively correlated with haemoglobin level. Relationship of haemoglobin with serum iron and TSAT level was statistically significant. Statistical analysis showed relationship between eGFR with haemoglobin and serum ferritin level was significant (P